Improved 3D velocity model for determining aftershock locations of the 2015 Gorkha, Nepal Earthquake - Chintan Timsina; James Mori; Masumi Yamada; Shiro Ohmi (Earth, Planets and Space)
Abstract The 2015 Mw 7.9 Gorkha earthquake in Nepal and its subsequent aftershock sequence, including the Mw 7.2 Kodari earthquake, which occurred on the eastern edge of the Gorkha mainshock, significantly impacted the region. Accurate aftershock locations are crucial for understanding the Main Himalayan Thrust (MHT) structure and regional seismic hazards. This study presents an improved 3D velocity model derived through tomographic inversion using data from the NAMASTE network, comprising 42 seismic stations that recorded aftershocks from June 2015 to May 2016. An initial 1D velocity model was refined into 2D and 3D models using a stepwise inversion approach, ensuring robust resolution in the region. The resulting velocity structure reveals distinct high-velocity zones corresponding to the mainshock slip region and low-velocity zones near the Kodari aftershock. The improved model provided better depth accuracy for relocated aftershocks, with most events clustering within 5 km of the MHT, improving consistency with known geological structures. The results highlight two seismic belts along the MHT: a northern belt near the downdip extent of interseismic coupling and a southern belt concentrated in distinct clusters outside the rupture area. This enhanced 3D velocity model clarifies the spatial relationship between aftershock distribution and the MHT, improving our understanding of seismic behavior in the Nepal Himalaya and supporting improved seismic hazard assessments. Graphical Abstract